Membrane processing : (Wiley-Blackwell, 2013)
The book is divided into four informal sections. The first part provides an overview of membrane technology, including the main scientific principles; the major membrane types and their construction; cleaning and disinfection; and historical development. The second part focuses on dairy applications including liquid and fermented milks; cheese; whey; and milk concentrates. The third part of the book addresses beverage applications including mineral waters, fruit juices and sports drinks, and the final part looks at membrane filtration in the production of beers, wines and spirits.